Pengaruh Model Inkuiri Terbimbing melalui Pembelajaran Praktikum terhadap Kemampuan Psikomotor Peserta Didik Kelas XI MIA di MAN 10 Jombang - Mucharommah Sartika Ami; Hasna Lailil Ma’rifah; Fatikhatun Nikmatus Sholihah (Jurnal Biologi dan Pembelajarannya (JB&P), 2021)
This study aims to determine the effect of guided inquiry models through practicum learning on the psychomotor abilities of class XI MIA students in MAN 10 Jombang. The method used is quantitative with a pre-experimental design in the form of one group pretest-posttest. Data collection was carried out through interviews, observations, and performance tests. The instruments used include interview guides, guided inquiry-based learning tools, learning implementation observation sheets, and students' psychomotor ability assessment sheets. The interview guide was used to conduct a needs analysis and interviews were conducted with biology teachers at MAN 10 Jombang. Guided inquiry-based learning tools were used to carry out guided inquiry-based practicum learning in this study. The number of samples of students used in this study was 15 people. The observation data on the implementation of learning were analyzed descriptively, while the data on the psychomotor abilities of students were analyzed parametrically using SPSS version 25.0 software. Guided inquiry-based practicum learning in this study was carried out well with a percentage of 79.4%. The psychomotor abilities of students at the posttest stage increased by 40% compared to the pretest stage. At the pretest stage, six students had very poor psychomotor abilities, while at the posttest stage there were no students with very poor psychomotor abilities. The results of the product-moment analysis show that the guided inquiry model through practicum learning has a significant effect on the psychomotor abilities of students, with a value of 0.769 and a significance level of 5%. The results of the regression analysis showed that guided inquiry-based practicum learning had an effect of 59.1% on the increase in students' psychomotor abilities. Based on the results of this study the teacher can apply guided inquiry-based practical learning to train or improve the psychomotor abilities of students.